GEO SA-BSAR Synchronization and MTI Algorithm Based on Direct Signal and Clutter Subspace - Chang Cui; Xichao Dong; Zhiyang Chen (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
Geosynchronous (GEO) spaceborne-airborne bistatic synthetic aperture radar, consisting of a GEO transmitter and an airborne multichannel receiver, is a potential moving target indication (MTI) system. However, such systems encounter synchronization challenges due to noncooperative transmission and reception. Besides, the inaccurate GEO orbital position for the MTI processor construction results in a low output signal-to-noise ratio (SNR) and reduced target detection probability. To address this, this article proposes a synchronization and MTI method based on direct signal and clutter subspace, which can enhance the output SNR for target detection even if the GEO orbital position is inaccurate. This method utilizes the direct signal to compensate for time and frequency synchronization errors. In addition, the residual error caused by the imprecise GEO orbit is estimated by approximating the clutter subspace. Next, a modified MTI processor is employed to suppress clutter and focus moving targets by using the residual error. Finally, the effectiveness of the proposed method is verified by numerical simulation experiments based on real IGSO orbital parameters.